Relevansi Pemikiran Filsafat Pendidikan Muhammad Natsir terhadap Krisis Moral dan Identitas Generasi Muslim Kontemporer. - Abdul Wafi; Musleh; Fahim Abu Ramadhan; Septiadi; Febry Suprapto (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
The moral and identity crisis afflicting the contemporary Muslim generation is a global phenomenon that reflects a disconnection between modern education and Islamic spiritual values. In this context, Muhammad Natsir’s philosophy of education serves as an essential conceptual foundation for reaffirming the orientation of Islamic education rooted in tawhid (monotheism), ethics (akhlaq), and the integration of knowledge. This study aims to analyze the relevance of Natsir’s educational philosophy to the challenges of moral decadence and identity disorientation faced by Muslim youth in the era of globalization. The method used is library research with a content analysis approach, examining Natsir’s major works such as Capita Selecta and relevant secondary literature. The results indicate that Natsir views education as a process of forming the insan kamil—a complete human being who harmonizes intellectuality, spirituality, and morality. Education, for Natsir, is not merely the transmission of knowledge but a transformation of character based on divine values. His educational philosophy emphasizes that moral and identity crises arise from the disintegration between knowledge and faith. The theoretical contribution of this research lies in reconstructing an Islamic educational paradigm based on tawhid and akhlaq as ethical and epistemological solutions to modern disorientation. Practically, this study offers an integral educational model relevant to curriculum reform and the moral identity formation of the Muslim generation at the global level.